PERAN PUBLIC RELATIONS (PR) UNIVERSITAS BRAWIJAYA DALAM ERA BADAN HUKUM PENDIDIKAN TINGGI (PTN-BH) - Aulia Luqman Aziz (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to determine the role of knowing, describing and analyzing the role of Public Relations (PR) of Brawijaya University in the Era of Higher Education Legal Entities (PTN-BH). Researchers want to know the role of PTN BH Public Relations in the city of Bandung as a communication facilitator, mediator and communication technician in the implementation of information disclosure policies. Researchers used a descriptive study with qualitative data types. Data collection was carried out using the method of literature study or literature review. The findings from this study indicate that Public Relations of Universitas Brawijaya has carried out its role. However, there are some things that require improvement to make it better. Therefore, the researcher suggests that UB's Public Relations should increase its evaluation activities regarding information disclosure, socialize the obligation to open information to the internal and external public and increase meetings that invite various parties both internally and externally UB to overcome the obstacles faced by UB's Public Relations.